Role of vitamin D in prevention of adverse maternal and perinatal outcome: a randomized controlled trial - S., Sujatha M.; R., Shruthi K.; ., Neelaharika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Vitamin D deficiency is thought to be common among pregnant women and is associated with adverse maternal and perinatal outcome. Maternal and foetal outcome in pregnant women with standard obstetric care was compared with women with additional vitamin D supplementation. Methods: A randomized comparative study was conducted on 100 patients attending the antenatal clinic at JSS Medical College and Hospital, Mysuru, Karnataka, India who were randomly grouped into group A (50 patients) who received standard obstetric care (500 mg calcium+200 IU vitamin D) and group B (50 patients) who received in addition to standard obstetric care supplementation of Vitamin D 1000 IU/day starting from 14 weeks of gestation till delivery. Vitamin D levels were assessed in both the groups with onset of labour by chemiluminescence immunoassay and obstetric and neonatal outcomes in both groups were compared. Results: High incidence of vitamin D deficiency (96%) in standard care group compared to vitamin D supplemented group ( p= <0.0001) was noted. The study showed significant reduction in risk of Preeclampsia (P=0.004), GDM (P= 0.02) and primary caesarean delivery (0.008) in Vitamin D supplemented group. Significantly high birth weight in vitamin D supplemented group, an increase in 320 grams in birth weight was noted (P <0.0001). Conclusions: There is a high incidence of subnormal vitamin D levels in antenatal women and is associated with maternal and neonatal adverse effects. Measuring Vitamin D levels and appropriate supplementation of higher dose of vitamin D is an effective strategy in prevention of adverse maternal and neonatal outcomes.